2010
DOI: 10.1021/ja907077e
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Libration of a Double-Decker Porphyrin Visualized

Abstract: Scanning tunneling microscopy has revealed the reorientation of one of the macrocyclic rings of the double-decker porphyrin complex [Ce(TPP-Fc)(C(22)OPP)] [TPP-Fc = 5-(4-(4-ferrocenylphenylethynyl)phenyl)-10,15,20-triphenylporphyrin; C(22)OPP = 5,10,15,20-tetrakis(4-docosyloxyphenyl)porphyrin] by 90 degrees between scans when the other ring is fixed on a surface. This libration was evidenced by monitoring the location of the appended ferrocene unit, which functioned as a molecular beacon signaling its position. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Similar effects were also observed in the case of [Ce(C 22 OPP)(TPP-Fc)], for which the ferrocene unit appeared higher in the pure array of the molecules than in the matrix of H 2 (C 22 OPP). 25 We have rarely encountered the parallel orientation for the present double-decker complex, in which the free-base porphyrin units are directed along the molecular row (see Fig. 1(b)).…”
Section: Self-assembled Monolayers Mixed With Free-basementioning
confidence: 85%
See 3 more Smart Citations
“…Similar effects were also observed in the case of [Ce(C 22 OPP)(TPP-Fc)], for which the ferrocene unit appeared higher in the pure array of the molecules than in the matrix of H 2 (C 22 OPP). 25 We have rarely encountered the parallel orientation for the present double-decker complex, in which the free-base porphyrin units are directed along the molecular row (see Fig. 1(b)).…”
Section: Self-assembled Monolayers Mixed With Free-basementioning
confidence: 85%
“…It was also hoped that the rotational behavior of the upper TPP-TPP fragment could be analyzed by making room around the double-decker complex, as was successfully done for [Ce(C 22 OPP)(TPPFc)], 25 which turned out to be difficult for the present molecule as described below. Figure 5 shows a couple of typical STM images prepared from a mixed solution of [Ce(C 22 OPP)(TPP-TPP)]…”
Section: Self-assembled Monolayers Mixed With Free-basementioning
confidence: 99%
See 2 more Smart Citations
“…7 Otsuki et al directly observed rotation of double-decker complexes on a surface using STM and evaluated the rotation rate (Figure 3). 8 Makiura et al reported the layer-by-layer surface preparation of a two-dimensional metalorganic framework (MOF) comprising a LangmuirBlodgett film of a network of porphyrin and copper ions. 9 Nishihara, Sasaki, Nakazato, and co-workers recently synthesized π-conjugated metal complex nanosheets comprising nickel bis(dithiolene) units via an interfacial reaction system containing the ligand in an organic layer and the metal ion in an aqueous layer.…”
Section: Interfacial Programming For Molecular Circuit Systemsmentioning
confidence: 99%